Effect of hydrocyclone size on microplastics separation: a computational fluid dynamics investigation - Dulyapat Thiemsakul; Shibo Kuang; Wiwittawin Sukmas; Eakarach Bumrungthaichaichan; Krittin Korkerd; Ratchanon Piemjaiswang; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (South African Journal of Chemical Engineering, 2025)
• Microplastics separation in hydrocyclones was simulated using three-phase CFD. • Geometric scale of the hydrocyclone and the velocity of the inlet were investigated. • As the hydrocyclone size decreased, the recovery of microplastics increased. • Higher inlet velocities improved recovery by amplifying centrifugal forces. Microplastics pose a significant environmental threat, particularly to aquatic ecosystems. Removing microplastics from water is a critical challenge due to their small size and widespread presence. In this study, the separation of polystyrene (PS) and polyethylene terephthalate (PET) microplastics in hydrocyclones was investigated using Computational Fluid Dynamics (CFD) simulations. A three-dimensional Eulerian-Eulerian multiphase model was employed to simulate the separation process, with water, air, and microplastics. The model demonstrated good agreement results, confirming the reliability of the simulation results. Two factors affecting hydrocyclone performance were investigated. The base hydrocyclone model was scaled down using factors ranging from 1.0 to 0.2 to investigate how size reduction influenced separation efficiency. The results showed that smaller hydrocyclones enhanced recovery (PS: 5.88 to 7.64%; PET: 7.79 to 14.86%) due to stronger centrifugal forces, while higher inlet velocities improved recovery but increased the pressure drop from 49 to 59 kPa, indicating a clear trade-off between separation efficiency and energy consumption. This increase was attributed to the higher centrifugal forces generated in smaller hydrocyclones, which more effectively pushed particles toward the walls, enhancing separation based on density. In addition, higher inlet velocities improved microplastic recovery by amplifying the centrifugal forces within the hydrocyclone, but this came at the cost of increased pressure drop and energy losses due to intensified turbulence and friction.
Keywords: Cyclone Separators and Fluid Dynamics; Granular flow and fluidized beds; Materials Engineering and Processing